Keanekaragaman Jenis Ikan di Danau Teluk Rasau, Pedamaran Kabupaten Ogan Komering Ilir Provinsi Sumatera Selatan - Mohammad Rasyid Ridho; Enggar Patriono (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2020)
The research about Fish Diversity in Teluk Rasau Lake, Pedamaran Ogan Komering Ilir Regency South Sumatera Province conducted in July 2014 and February 2015. The aim of this study were to analyzed diversity and abundance of fish at that area. Samples collected by using purposive sampling method. Result of the study in July 2014 and February 2015 were 18 fish species with diversity index (H’) were 2.81 and 2.91, respectively. Meanwhile, fish diversity and fish abundance in July 2014 were greater than February 2015 which were 99.9% and 763 individu, 99.5% and 120 individu, respectively.